Protection of Aroma Volatiles in a Red Wine with Low Sulphur Dioxide by a Mixture of Glutathione, Caffeic Acid and Gallic Acid - Roussis, I.G.; Patrianakou, M.; Drossiadis, A. (South African Journal of Enology and Viticulture, 2013)
The levels of several esters and other volatiles in Merlot-Cabernet Sauvignon blend red wines with typical sulphur dioxide (35 mg/L), with low sulphur dioxide (25 mg/L), and with low sulphur dioxide (25 mg/L) plus a mixture of antioxidants (glutathione 20 mg/L, caffeic acid 60 mg/L and gallic acid 20 mg/L), were evaluated at bottling, and after 18 and 36 months of ageing. Most volatiles decreased during wine storage. At bottling and after 18 months of storage, all three wines exhibited similar levels of volatiles. After 36 months of storage, wines with low sulphur dioxide exhibited lower levels of many volatiles, such as ethyl acetate, ethyl hexanoate, ethyl octanoate and 2-phenylethanol. On the other hand, wines with low sulphur dioxide plus the mixture of antioxidants exhibited similar levels of most volatiles in comparison with wines with typical sulphur dioxide. The present results indicate that a mixture of glutathione, caffeic acid and gallic acid can protect esters and other volatiles in young red wine with low sulphur dioxide, and can replace part of sulphur dioxide typically used.